Seni Rupa Sebagai Alat Komunikasi: Membangun Bahasa Visual pada Anak Usia Dini - Masruroh, Ummi (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This research discusses using visual arts as a visual communication tool in early childhood, focusing on how visual arts can help children express their feelings and ideas. This research focuses on the role of visual arts in children's social-emotional and cognitive development and how teaching visual arts can develop children's visual language as a means of communication. This research aims to identify and understand how visual arts can be used as an emotional and social communication tool for young children. The method used is a qualitative approach with direct observation of children's fine art activities, interviews with educators, and analysis of artwork produced by children. The results show that fine art is more than just a medium for creative expression; it is also a means for children to communicate their feelings and experiences through colour, shape, and composition. This research makes an important contribution to developing early childhood fine arts curriculum, emphasising visual communication as the main skill that needs to be created, not just technical drawing skills. In conclusion, fine arts can enrich children's visual communication skills, crucial in supporting their social, emotional, and cognitive development.